2016
DOI: 10.3390/vaccines4040044
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Prime-Boost Vaccination with OVA Entrapped in Self-Adjuvanting Archaeosomes Induces High Numbers of OVA-Specific CD8+ T Cells that Protect Against Subcutaneous B16-OVA Melanoma

Abstract: Homologous prime-boost vaccinations with live vectors typically fail to induce repeated strong CD8+ T cell responses due to the induction of anti-vector immunity, highlighting the need for alternative delivery vehicles. The unique ether lipids of archaea may be constituted into liposomes, archaeosomes, which do not induce anti-carrier responses, making them an ideal candidate for use in repeat vaccination systems. Herein, we evaluated in mice the maximum threshold of antigen-specific CD8+ T cell responses that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…injection and their safety profile was evaluated. Dose levels of archaeosomes used for vaccination studies in mice are typically between 0.3 -1.5 mg, 5,6,9 and therefore 1 mg was selected to represent a typical vaccine dose level, whereas 10 mg of SLA/LA allowed for the evaluation of safety parameters at lipid levels approximately 10-fold higher than normally administered in vivo. No significant differences were seen between male and female mice, and as such, data from female and male mice receiving similar treatments were combined for presentation purposes.…”
Section: Safety Of Sla/la Archaeosomes Following Intramuscular Injectmentioning
confidence: 99%
“…injection and their safety profile was evaluated. Dose levels of archaeosomes used for vaccination studies in mice are typically between 0.3 -1.5 mg, 5,6,9 and therefore 1 mg was selected to represent a typical vaccine dose level, whereas 10 mg of SLA/LA allowed for the evaluation of safety parameters at lipid levels approximately 10-fold higher than normally administered in vivo. No significant differences were seen between male and female mice, and as such, data from female and male mice receiving similar treatments were combined for presentation purposes.…”
Section: Safety Of Sla/la Archaeosomes Following Intramuscular Injectmentioning
confidence: 99%
“…Archaeal lipid adjuvants are a good potential candidate for use in combination with CPI's, as evidenced by their proven safety and efficacy in mice [19,44]. In multiple pre-clinical studies, they have been shown to activate antigen-specific CD8 + T cell responses [15,19,26,27] and generate protective immunity in tumor models, e.g., B16-OVA melanoma [7,13,19,23,26,27], and against multiple infectious diseases, e.g., H1N1 influenza [11], Listeria monocytogenes [7,12], Trypanosoma cruzi [13] and Mycobacterium tuberculosis [14]. When compared to commonly used commercial adjuvants, such as Poly(I:C) or Montanide, archaeal lipid vaccines were found to elicit equal or greater antigen specific CD8 + T cell-mediated cytotoxicity and IgG responses [10].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor and spleen samples were collected at various time points during the study when the mice had reached their humane endpoint. Spleen and tumor samples were processed as described previously [15,27]. Briefly, spleen samples were mashed between two frosted glass slides to obtain a single-cell suspension.…”
Section: Cellular Processing and Detection Of Ova-specific Cd8 + T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional archaeosomal formulations consisted of liposomes formed from total polar lipids (TPL) derived from archaea such as the methanogen Methanobrevibacter smithii (MS). These archaeosomes were shown to effectively activate professional antigen-presenting cells [14][15][16] and generate robust cellular and humoral immune response to encapsulated antigen in both cancer and infectious disease models [11,12,17]. More recently, a novel simpler semi-synthetic archaeosome formulation composed of a sulfated disaccharide group covalently linked to the free sn-1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA), has been developed [18].…”
Section: Introductionmentioning
confidence: 99%